2020
DOI: 10.17718/tojde.803423
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Digital Citizenship: Preschool Teacher Candidates vs. Computer Education and Instructional Technology Teacher Candidates

Abstract: The main goal of this study is to determine the digital citizenship perceptions and digital citizenship levels of preschool teacher candidates in terms of digital rights and responsibilities, digital security and digital law by comparing them with Computer and Instructional Technologies teacher candidates' perception. To this end, we worked with 80 teacher candidates in total. Both qualitative and quantitative research methods were employed. To identify participants' digital citizenship levels, a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
5
0
4
Order By: Relevance
“…According to Ngalim (2014) , people should evade language impoliteness in verbal and written communication based on the guidance of the Qur’an and Hadith. In this regard, Hasjim (2013) discussed language politeness in Islam, while ( Tobing et al., 2013 ) stated that it is a pillar of character building ( Elmali et al., 2020 ; Leone and Fink, 2017 ). Additionally, previous studies did not discuss the interrelation between the values of prophetic education and positive politeness.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ngalim (2014) , people should evade language impoliteness in verbal and written communication based on the guidance of the Qur’an and Hadith. In this regard, Hasjim (2013) discussed language politeness in Islam, while ( Tobing et al., 2013 ) stated that it is a pillar of character building ( Elmali et al., 2020 ; Leone and Fink, 2017 ). Additionally, previous studies did not discuss the interrelation between the values of prophetic education and positive politeness.…”
Section: Resultsmentioning
confidence: 99%
“…It showed that the usage of the Internet does not increase the digital citizenship of an individual if it is not utilized properly; however, the nature of academic specializations and knowledge do contribute to the digital knowledge of an individual. Elmali et al (2020) determined the perceptions of pre-school teachers regarding digital citizenship and their level of digital citizenship. The study consisted of 80 teaching candidates, employing quantitative and qualitative methods, employing surveys and interviews to understand the participants' perceptions better.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The general purposes of those studies were to determine the elementary, secondary, high school and university level students' characteristics related to the elements of digital citizenship Al Raqqad, 2020;Çebi & Özdemir, 2019;Çepni et al, 2014;Jwaifell, 2018;İridağ, 2020;Korucu & Totan, 2019;Martin et al, 2020b;Nazik et al, 2020;Öztürk, 2019;Ünal, 2017;Vural, 2016;Yalçınkaya & Cibaroğlu, 2019). Some others studies aimed to identify the characteristics of educational administrators, teachers or preservice teachers (Akcil et al, 2016;Arcagök, 2020;Aslan, 2016;Ata & Yıldırım, 2019;Aygün, 2019;Aygun & İlhan, 2020;Dedebali & Daşdemir, 2019;Dere & Yavuzay, 2019;Elmalı et al, 2020;Görmez, 2017a;Hollandsworth et al, 2011Hollandsworth et al, , 2017Kabataş, 2019;Kaya & Kaya, 2014;Xu et al, 2019;Yılmaz & Doğusoy, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%